Fecal pH and starch concentrations in relation to prevalence of Escherichia coli O157 in feedlot cattle - Depenbusch, Brandon (Kansas State University, 2008)
Escherichia coli O157, a food-borne human pathogen, causes hemorrhagic colitis and hemolytic uremic syndrome. Cattle are a major reservoir and the organism resides in the hindgut and is shed in the feces. Cattle feces are a major source of food and water contamination. Houseflies feed on cattle manure and are a source of E. coli O157 transmission. We have observed that houseflies have an affinity for a steam-flaked corn product (SFC-36) made from tempered whole corn that is more ruminally digestible than the traditional SFC (SFC-18). Therefore, we investigated whether SFC-36 diets contained and resulted in higher E. coli concentrations in the feces of cattle compared to SFC-18 diets. Concentrations of E. coli were not different between the two SFC diet samples, but resulted in higher coliforms in diets containing the SFC-36 after exposure to the environment. However, E. coli concentrations in feces from cattle fed the two diets were similar. In fact, cattle fed the diet containing SFC-18 flakes actually shed higher concentrations of coliforms. This led us to speculate that starch digestion may have an effect on the growth of E. coli O157 in the hindgut. We determined whether fecal E. coli O157 was related to fecal starch concentration. Steers (n=263) were sampled for E. coli O157 and fecal starch concentration determinations. Steers positive for E. coli O157 contained 21% more (P < 0.05) fecal starch than steers that were negative for E. coli O157. We attempted to alter the concentration of starch escaping rumen fermentation by feeding diets based on SFC and dry-rolled corn (DRC) to 30 heifers prescreened for being culture positive for fecal E. coli O157. Heifers were sampled for feces and by rectoanal mucosal swab (RAMS) weekly to monitor fecal pH and fecal starch concentration, and prevalence of E. coli O157. Based on RAMS, prevalence of E. coli O157 tended to be higher (P = 0.08) for heifers fed SFC than DRC diet. Fecal starch and pH were similar (P > 0.05) between positive- or negative-E. coli O157 heifers. Apparently, fecal E. coli O157 was not related to fecal pH or starch concentration in cattle.
Keywords: Escherichia coli; Cattle; Fecal starch; Fecal pH; Agriculture, Animal Culture and Nutrition (0475)